Vaping and e-cigarettes: A public health warning or a health promotion tool? - van Teijlingen, Edwin; Mahato, Preeti; Simkhada, Padam; van Teijlingen, Cameron; Asim, Mohammad; Sathian, Brijesh (Nepal Journal of Epidemiology, 2019)
Over the past decade the use of electronic cigarettes (e-cigarettes) or so-called vaping has become increasingly popular in many parts of the world. The e-cigarette is a battery-operated device which releases vapours of flavoured nicotine instead of tobacco smoke. The e-cigarette is a way to consume nicotine which gives the ‘high’ without the consumption of tar and other cancerous chemicals normally present in conventional tobacco cigarettes.